(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Writing is one of the essential language skills in English learning, particularly for vocational high school students who are expected to acquire practical communication competencies relevant to the workplace. However, English writing skills remain a major challenge for many students, largely due to instructional practices that emphasize grammatical accuracy and vocabulary mastery in isolation, rather than contextual and functional language use. The Systemic Functional Linguistics (SFL) approach conceptualizes language as a meaning-making resource within specific social contexts and therefore has the potential to enhance students’ writing skills in a more contextualized, functional, and structured manner. This study aimed to evaluate the effectiveness of an SFL-based instructional approach in improving English writing skills among students at SMK Swasta YAPIM Biru-Biru. A pretest–posttest research design was employed involving 100 vocational school students as participants. Students’ writing skills were assessed before and after the implementation of SFL-based instruction using standardized writing assessment criteria, and the data were analyzed using the Wilcoxon signed-rank test. The results revealed a significant improvement in students’ writing performance following the intervention. The proportion of students categorized as having good writing skills increased from 28% in the pretest to 69% in the posttest, while those in the poor category decreased from 72% to 31%. The Wilcoxon test yielded a Z value of −7.561 with a significance level of p = 0.000 (p < 0.05), and no negative ranks were identified, indicating that the intervention did not result in any decline in students’ writing ability and produced exclusively positive effects. These findings demonstrate that the SFL-based approach effectively supports students in understanding text structure, social functions of language, and appropriate linguistic features in writing. In conclusion, the implementation of Systemic Functional Linguistics significantly enhances students’ English writing skills and contributes to the promotion of quality education in line with the objectives of Sustainable Development Goal (SDG) 4.